2015
DOI: 10.1093/cvr/cvv279
|View full text |Cite
|
Sign up to set email alerts
|

Succinate dehydrogenase inhibition with malonate during reperfusion reduces infarct size by preventing mitochondrial permeability transition

Abstract: Succinate dehydrogenase inhibition with malonate at the onset of reperfusion reduces infarct size in isolated mice hearts through reduction in ROS production and mitochondrial permeability transition pore opening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 41 publications
8
125
0
1
Order By: Relevance
“…9). This scenario is consistent with recent experimental findings that SDH inhibition with malonate at the start of reperfusion inhibits both ROS production and PTP opening/cell damage (45). It is also consistent with the observation that the complex I inhibitor rotenone protects against I/R injury by suppressing RET and inhibiting the initial PTP opening that activates succinate-driven ROS production by complexes II and III.…”
Section: Relevance To I/r Injurysupporting
confidence: 92%
“…9). This scenario is consistent with recent experimental findings that SDH inhibition with malonate at the start of reperfusion inhibits both ROS production and PTP opening/cell damage (45). It is also consistent with the observation that the complex I inhibitor rotenone protects against I/R injury by suppressing RET and inhibiting the initial PTP opening that activates succinate-driven ROS production by complexes II and III.…”
Section: Relevance To I/r Injurysupporting
confidence: 92%
“…19 Calpain activation occurring upon normalization of intracellular pH in cells with Ca 2+ has been demonstrated to contribute to cardiomyocyte death. 20 Reactive oxygen species may induce MPTP opening, and interventions attenuating mitochondrial ROS production can prevent MPTP opening and reduce MI size, 21 but they also have extra-mitochondrial targets, the importance of which needs to be clarified. A potentially important target of ROS is the tetrahydrobiopterin–eNOS complex, which may be dissociated by oxidation, resulting in peroxynitrite formation and reduced NO availability.…”
Section: Why Has It Been So Difficult To Prevent Myocardial Reperfusimentioning
confidence: 99%
“…Indeed, recent work in the isolated mouse heart has demonstrated that the administration of malonate during the first 15 minutes of reperfusion was cardioprotective only through the inhibition of succinate reoxidation and the reduction in ROS production and mPTP opening. 98 Whether this important result can be translated to in vivo models, however, remains to be determined.…”
Section: Pharmacological Inhibitors Of the Respiratory Chain As Theramentioning
confidence: 99%